Extraction System of Upgraded AVF Cyclotron of RCNP. (November 2019) - Nakao, M; Fukuda, M; Hara, S; Hara, T; Hatanaka, K; Kamakura, K; Kanda, H; Koay, H W; Morinobu, S; Morita, Y; Nagayama, K; Saito, T; et al.
Abstract: At the Research Center for Nuclear Physics (RCNP) of Osaka University, the demand for both high-intensity and high-quality beam has been increasing. New injection, acceleration, and extraction system of the AVF cyclotron are under development to meet the demand. Extraction system was designed to increase the extraction efficiency since beam loss at electrodes or apertures makes unacceptable radio activation of apparatus when the beam intensity increased. Simulation study confirmed that 10 MeV protons, 65 MeV protons and 140 MeV 4 He 2+ particles with emittance of 2 mm × 3 mrad can pass through the newly designed extraction system and the existing beam transport line.